GREEN HUMAN RESOURCE PRACTICES AND SUSTAINABLE DEVELOPMENT OF BUSINESS ORGANISATIONS IN THE MANUFACTURING SECTOR OF THE NIGERIAN ECONOMY - Oginni Babalola Oluwayemi; Abel Segun Adesanya; Hammed Omotola Ojodu; Victor Ajibayo Adeyeye (Economic Review)
The effect of climate change has heightened a significant interest in environmental-related areas of human endeavor thus explaining why sustainability is the major concern of stakeholders in the industrial world without any exemptions. Green human resource management (GHRM) practices became an important factor in reducing the ecological footprints and climate change brought about by human activities. Thus, the study set out to identify the place of GHRM practices in sustainable development and examine the influence exerted by components of GHRM on sustainable development using tobacco and beverage organizations in the manufacturing organizations as the unit of analysis. The study adopted a multi-stage sampling technique, and 268 copies of the questionnaires were analyzed. The study identified green recruitment and selection (GRS) practices, green education (T&D) practices, and green compensation practices among the major components of GHRM dominant and prevailing in manufacturing organizations. It was found that GHRM exerted a greater influence on sustainable development after establishing a linear relationship between GHRM and sustainable development at 0.01 and 0.05 Sig. level. It was concluded that a high premium should be placed on GRS practices, T&D practices, and green compensation practices, and recommended that management should develop GHRM objectives that would be tailored towards sustainable development.